2015
DOI: 10.1371/journal.pone.0120635
|View full text |Cite
|
Sign up to set email alerts
|

Two Arginine Residues Suppress the Flexibility of Nucleosomal DNA in the Canonical Nucleosome Core

Abstract: The dynamics of nucleosomes containing either canonical H3 or its centromere-specific variant CENP-A were investigated using molecular dynamics simulations. The simulations showed that the histone cores were structurally stable during simulation periods of 100 ns and 50 ns, while DNA was highly flexible at the entry and exit regions and partially dissociated from the histone core. In particular, approximately 20–25 bp of DNA at the entry and exit regions of the CENP-A nucleosome exhibited larger fluctuations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
7
26
0
Order By: Relevance
“…6). The behavior of the H3/H4 tails is similar to previous study (29), and not altered by the loss of H2A/H2B.…”
Section: Interactions Between Histone Tails and Dnasupporting
confidence: 87%
“…6). The behavior of the H3/H4 tails is similar to previous study (29), and not altered by the loss of H2A/H2B.…”
Section: Interactions Between Histone Tails and Dnasupporting
confidence: 87%
“…The free energy profiles were cytokinesis defects [19]. We previously carried out molecular dynamics simulations on the canonical and CENP-A nucleosome core particles, which showed that two Arg residues, R49 and R52, in the helix are responsible for the stability of DNA at both ends of DNA in the canonical nucleosome [7]. In the CENP-A NCP, Lys corresponds to these residues and is likely to lose a hydrogen bond with DNA more easily than Arg.…”
Section: Umbrella Sampling and Free-energy Profile Using Whammentioning
confidence: 99%
“…The conformational parameters were calculated using X3DNA [21]. The missing histone tails of CENP-A NCP were not modelled because the simulation system was set as similar as possible to our previous simulation of H3 NCP [7]. The effect of the histone tails, likely to be of significance, will be the subject of a future investigation.…”
Section: Atomic Modelsmentioning
confidence: 99%
See 2 more Smart Citations